EYES IN THE SKY. - Edward, Olivia (Geographical (Geographical Magazine Ltd.), 2011)
The article discusses the growing use of satellite imagery to highlight human rights abuses around the world. It states that with the costs of satellites dropping, more images of remote areas are becoming available, thanks to firms like the GeoEye Foundation and Google Earth. As certain countries and companies sometimes deny journalists and aid workers access to certain areas, satellite imagery can provide evidence of violations. It claims, however, that only a few satellites are in orbit, and they do not always succeed in imaging certain areas.